2008
DOI: 10.11646/zootaxa.1750.1.6
|View full text |Cite
|
Sign up to set email alerts
|

A new species of night-lizard of the genus Lepidophyma (Squamata: Xantusiidae) from the Cuicatlan Valley, Oaxaca, Mexico

Abstract: A new species of Lepidophyma from the Biosphere Reserve area of Tehuacan-Cuicatlan, Oaxaca, Mexico, is described. This new species, Lepidophyma cuicateca sp. nov., is known from two areas in the Cuicatlan Valley. Lepidophyma cuicateca sp. nov. is a member of the Lepidophyma gaigeae species Group and is characterized by its small body size, small size of tubercular body scales, poorly differentiated caudal whorls and interwhorls, and relatively large dorsal, ventral and gular scales. It lives in shady places, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Fourteen of the 18 recognized Lepidophyma species (Bezy and Camarillo 2002; Canseco‐Márquez et al 2008) were collected for DNA sequencing and subsequent phylogenetic and population genetic analyses (Appendices S1 and S2). Four species not included in this study ( L. lineri, L. chicoasense, L. tarascae , and the recently described L. cuicateca ) have extremely restricted distributions in southern Mexico and are either very rare or extinct (Bezy and Camarillo 2002; Canseco‐Márquez et al 2008). Several other species also have very localized distributions and are extremely difficult to collect; out of necessity, five species are represented here by single tissue samples, and two species each are represented by two and three samples, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen of the 18 recognized Lepidophyma species (Bezy and Camarillo 2002; Canseco‐Márquez et al 2008) were collected for DNA sequencing and subsequent phylogenetic and population genetic analyses (Appendices S1 and S2). Four species not included in this study ( L. lineri, L. chicoasense, L. tarascae , and the recently described L. cuicateca ) have extremely restricted distributions in southern Mexico and are either very rare or extinct (Bezy and Camarillo 2002; Canseco‐Márquez et al 2008). Several other species also have very localized distributions and are extremely difficult to collect; out of necessity, five species are represented here by single tissue samples, and two species each are represented by two and three samples, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The genus extends from northern Mexico through Central America to Panama (Fig. 2), and currently 18 species are recognized (Bezy and Camarillo 2002; Canseco‐Márquez et al 2008). In Lepidophyma reticulatum (Costa Rica) all known individuals are female; L. flavimaculatum populations in Panama and south‐eastern Costa Rica lack males, whereas northern populations contain both sexes and appear to be bisexual.…”
mentioning
confidence: 99%
“…Members of Lepidophyma are generally restricted to mesic habitats, although several species (e.g. L. cuicateca, L. gaigeae, L. occulor, L. radula) have been found in semi-arid interior valleys which are covered by low growing tropical deciduous forest and semi-desert (Bezy and Camarillo 2002;Canseco-Márquez et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this commendable effort, it appears that the diversity in the genus remains underestimated and new species continue to be discovered. Currently, 22 species are recognised as valid, of which five were described in the last two decades (Canseco-Márquez et al 2008;García-Vázquez et al 2010;Palacios-Aguilar et al 2018;Arenas-Moreno et al 2021; Lara-Tufiño and Montes de Oca 2021). Molecular analyses have shown that additional taxa might need to be recognised (Noonan et al 2013).…”
Section: Introductionmentioning
confidence: 99%